PREREQUISITES FOR EFFECTIVE DEFENSE IMPLEMENTATION DURING THE TRIAL PHASE - Ghazinyan, Gagik; Hovhannisyan, Lusine (State and Law, 2025)
This article seeks to examine the prerequisites for ensuring effective defense during the trial phase. The authors first analyze the right to defense, its significance, and its role within the framework of criminal procedural principles. Particular attention is paid to the court’s critical role as the guarantor of these principles in securing effective defense. The study further delves into the restrictions applied to defense counsel, which may arise at either legislative or customary levels. Fundamental principles such as adversarial proceedings, equality of arms, the right to cross-examine witnesses, challenging the admissibility of evidence, delivering closing arguments, and presenting positions on the application or interpretation of the law are identified as crucial components for achieving effective defense. The authors conclude that the existing regulatory framework for the submission of new evidence—limited exclusively to the phase of supplementing the evidence under review—can be perceived as an unwarranted limitation.